Creative approaches to working with older people in the public realm. Issue 1 (4th March 2014) - Baker, Daniel
Abstract : Purpose: – The purpose of this paper is to illustrate practical examples of arts projects that have successfully engaged older people in the public realm and to stimulate debate and provide practical insights for the arts, planning and social care sectors. Design/methodology/approach: – The paper presents research gathered during an international fellowship supported by the Winston Churchill Memorial Trust to the USA, New Zealand and Australia. A selection of the projects researched are included, to illustrate three key approaches to working creatively with older people in the public realm: engaging older people in creative retelling of public histories; enabling older people to become individual artists in the public eye; creating performances by and with older people in the public realm. Findings: – The paper finds that the arts can offer a range of practical methods for engaging older people in the public realm which have a number of potential outcomes: increasing their visibility in public life; increasing their active role in communities; and exploring important questions about the public realm and ageing. Practical implications: – Older people can be "invisible" and feel threatened in public life and the public realm, however, arts projects can offer a number of ways to increase their visibility and agency in public spaces and services, particularly through enabling and supporting their creative expression and foregrounding communication and collaboration. Originality/value: – The paper illustrates a number of key projects from the first major international research project into creative interventions involving older people in the public realm.